Toxidez cianogênica em folhas e raízes de mandioca (Manihot esculenta Crantz) - F Teles, F F; Silveira, A J; Batista, C M; G Feitosa, E P; M Rezende, J L (Revista Ceres, 2025)
The HCN content of leaves and roots of cassava (M. esculenta Crantz) was determined on ten clones cultivated in the State of Minas Gerais, Brazil. The results ranged from 0,086 to 0,300 mg/g in the roots, and from 0,173 to 0,478 mg/g in the leaves. A negative correlation (r = — 0,382) was observed.